Nature unsettled: How knowledge and power shape 'nature-based' approaches to societal challenges. (November 2020) - Woroniecki, Stephen; Wendo, Hausner; Brink, Ebba; Islar, Mine; Krause, Torsten; Vargas, Ana-Maria; Mahmoud, Yahia
Highlights: Nature is neither passive nor external to human society but expressed in frames. Frames are modes of expression that transmit power between social actors. Power affects nature-based practices and knowledge produced about them. We demonstrate these links in five cases with a social-change agenda. We show how frames of nature condition the potential for social transformation Abstract: Nature-based solutions (NbS) are gaining traction in high-level, decision-making arenas as a response to global policy challenges. Claiming to be transformative and pluralistic, NbS aim to resolve societal problems through a focus on nature, which is understood to be a benign ally. This uncritical framing of nature may have unintended and inequitable consequences that undermine the emancipatory potential of NbS. In this paper, we highlight the need to pay attention to epistemic and power dimensions that tend to be hidden in NbS. We assume that nature is neither passive nor external to human society, but is instead expressed in frames (reifying modes of expression) that reflect both knowledge and power in social encounters where NbS are used. Drawing upon five cases, we analyse how particular ways of framing nature express and reinforce the power relations that structure people's interactions. Each of the five cases relies on a nature-based frame to produce knowledge on climate adaptation, peacebuilding and justice. The analysis reveals how frames of nature are enacted in particular contexts, and how this conditions the potential for societal transformation towards sustainability and pluralistic knowledge. We demonstrate how frames of nature can constrain or enable opportunities for various groups to respond to environmental change. We discuss how the NbS paradigm might better incorporate diverse, situated knowledge and subjectivities, and conclude that this will require a more critical evaluation of NbS practice and research.